THE RELATIONSHIP BETWEEN OBESITY AND SELF-ESTEEM IN FEMALE ADOLESCENTS IN GRADE XII MAN I, KOTA BANDA ACEH - Auna Putri; Eva Purwita; Cut Nurhasanah; Irma Seriana (Department of Midwifery, Health Polytechnic of Aceh, 2024)
Background: Obesity is the accumulation of excessive fat in adipose tissue that can cause health problems among adolescents; untreated obesity can impact their psychological well-being. Obesity affects the psychological development of adolescents. The psychological issues that arise include self-esteem disorders related to their perception of their appearance. Issues with self- esteem lead to feelings of dissatisfaction with oneself, low self-confidence, feelings of being distanced by peers, and even depression. Subject and Method: This study is observational with a cross-sectional approach. The sample consists of 56 female adolescents in the twelfth grade at MAN 1 Banda Aceh, using a total sampling technique. Data analysis employed the chi-square test. Result: The research findings indicate that 29 individuals (56.8%) of female adolescents experience obesity I (BMI 25-29.9) and have low self-esteem. Female adolescents with obesity II exhibit low self-esteem in 5 cases (100%). A significant relationship exists between obesity and self-esteem among the twelfth-grade female adolescents at MAN 1 Banda Aceh, with a p-value of 0.000 (p<0.005). Conclusion: Obesity causes a decrease in self-esteem among the twelfth-grade female adolescents at MAN 1 Banda Aceh.